Fair Trade Rebels : Coffee Production and Struggles for Autonomy in Chiapas - Naylor, Lindsay (Book collections on Project MUSE., 2019)
"Fair Trade Rebels is based on extensive fieldwork among rural coffee and corn farmers in Chiapas, Mexico. Examining these farmers' everyday experiences of resistance and daily practice as they seek to address inequalities locally in what is really a global corporate agricultural chain, Naylor is interested in how these fair trade struggles are part of broader efforts on the part of local agricultural actors to create dignified livelihoods"--